On a Simple Dynamics Model of Interaction between Oasis and Climate - 吴凌云 巢纪平 符淙斌 潘晓玲 (Advances in atmospheric sciences, 2003)
This paper constructs a coupled system of oasis and atmosphere based on an oasis evolvement model by adding atmospheric motion to discuss the problem of oasis evolvement and its effects on regional climate.The results indicate that the range and scope of the negative temperature anomalies become larger when the oasis cover fraction increases. Correspondingly, the positive temperature anomalies becomes smaller in the desert no matter in summer or spring. And the variability is more obvious in summer than in spring.So it may be concluded that the oasis not only maintains and develops itself but also develops partial air over the desert into an oasis climate.